Implementation of Entrepreneurial Government in Makassar City Government - Muhammad Aris; Andi Agustang; Andi Muhammad Idkhan (Program Pascasarjana Universitas Negeri Makassar, 2021)
The concept of entrepreneurship in the government sector is very important and strategic to be input into the mindset and culture set of the state government apparatus. That is, the fundamental point is to organize the orientation of the government apparatus to be more adaptive, responsive, creative, innovative, professional, and visionary, to serve and capture every opportunity. The entrepreneurial spirit of government in the public sector is an ideal concept in the context of utilizing resources to improve the quality of public services and public trust more efficiently, effectively and more productively. However, it should be realized that even though the government adopts the principles of the private sector, the government's orientation is non-profit but to serve. This paper attempts to articulate how to implement entrepreneurship government in the Makassar City Government.